Aplikasi metode tahanan jenis dalam studi geologi karst Gua Seropan di Gunung Kidul, Yogyakarta - Pulung A. Pranantya; Nurlia Sadikin (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
In terms of geology, most areas in south of the Gunungkidul District in Central Java consist of the Wonosari formation limestone. The land is generally very dry and source of raw water is also difficult to reach. Findings on the existence of underground river in caves, however, indicate the potential amount of water within the area, especially in the eastern part of the Gunungkidul District. Although limited information available, some fishermen have discovered that Seropan cave contains fresh water source. This cave is situated at 65 m below the cliff. Initial exploration, which done using a multichannel resistivity method, confirmed the availability of freshwater in the cave and underground river. The isopach of cave depth is found in ranges of 80 200 m below the ground surface. The water of Seropan cave can be utilized by implementing pipeline or by drilling at the suggested point based on the interpretation results, i.e. 110o2223.6388 EL 8o42.874 SL. [DY1][PP2][DY1]Perbaiki grammarIn terms of geology, most areas in south of Gunungkidul District in Central Java consist of the Wonosari formation limestone. The land is generally very dry and source of raw water is also difficult to reach. Findings on the exixtence of underground river in caves, however, indicate potential amount of water within the area especially in eastern part of Gunungkidul District. Although limited information available, some fishermans has discovered that Seropan cave contain fresh water source. This cave is situated at 65 m below the cliff. Initial exploration, which done using multichannel resistivity method, confirmed the availability of freshwater in the cave and underground river. The iso pach of cave depth is found in ranges of 80 200 m below the ground surface. The water of Seropan cave can be utilized by implementing pipeline or by drilling at the suggested point based on the interpretation results i.e. 110o2223.6388 EL 8o42.874 SL.[PP2]Sudah diperbaiki